Комунікативні властивості студентів-психологів, схильних до лідерства - Підбуцька, Ніна Вікторівна; Книш, Анастасія Євгенівна; Богдан, Жанна Борисівна; Чебакова, Юлія Григорівна (Кам'янець-Подільський національний університет імені Івана Огієнка, 2021)
Дослідження присвячене темі комунікативних властивостей студентів-психологів, що схильні до лідерства. Тема дослідження зумовлена популярністю спеціальності "Психологія", що зростає, і необхідністю вдосконалення освітніх програм не тільки в напрямі забезпечення ключових фахових компетентностей, а й у напрямі розвитку soft skills, до яких відносяться лідерство та комунікативні здібності. Акцент робиться на необхідності визначення особливостей комунікативних особливостей майбутніх психологів схильних до лідерства з метою подальшої розробки індивідуалізованих програм розвитку лідерства студентів цього професійного напрямку.

The research is devoted to the topic of communicative traits of students-psychologists who are inclined to leadership. The research topic is due to the growing popularity of the specialty "Psychology" and the need to improve educational programs not only in the direction of providing key professional competencies, but also in the development of soft skills, which include leadership and communication skills. Emphasis is placed on the need to determine the features of communicative skills of future psychologists inclined to leadership in order to further develop individualized programs for leadership development of students in this professional field. The study involved 60 students of 3–4 courses studying in the educational program "Psychology". The following methods were used in the study: B. Bass's multifactor questionnaire of leadership, T. Leary's method of diagnostics of interpersonal relations, R. McCray's and T. Costa's five-factor personality questionnaire. According to the results of the study, it was determined that most students have an average level of leadership qualities. All factors of transformational leadership are well developed in psychologists, but the most pronounced are influence and management. The dominant types of interpersonal relationships in students with a high level of leadership are authoritarian style and friendly, and with low – friendly and altruistic. Personal characteristics of psychologists: with a high level of leadership: extraversion (optimistic, active and energetic), commitment (kind and sensitive); with a low level: introversion (insecure, closed and sensible), isolation (independent, independent and cold in relation to others). In both study groups were found: self-control (responsible, accurate and persistent), emotional stability (emotionally mature, calm and realistic) and expressiveness (emotionality and easy attitude to life).
Communicative traits of students-psychologists with tendency to leadership
Keywords: психологія; навчальний процес; професійний розвиток; лідерські якості; leadership; psychologists; communicative properties; professional development; future specialists